Odpowiedzi

2010-03-16T19:48:34+01:00
Szukając miejsc zerowych y=0

a)y=x²-x-20
x²-x-2=0

Δ=b²-4ac=(-1)²-4*1*(-2)=1+8=9
√Δ=√9=3

x₁=(-b+√Δ)/2a=(1+3)/2=4/2=2
x₂=(-b-√Δ)/2a=(1-3)/2=-2/2=-1

b)y=x²-x-20
x²-x-20=0

Δ=b²-4ac=(-1)²-4*1*(-20)=1+80=81
√Δ=√81=9

x₁=(-b+√Δ)/2a=(1+9)/2=10/2=5
x₂=(-b-√Δ)/2a=(1-9)/2=-8/2=-4

c)y=x²-6x+9
x²-6x+9=0

Δ=b²-4ac=(-6)²-4*1*9=36-36=0
√Δ=√0=0

x₁=-b/2a=6/2=3
x₂=x₁ (JEDNO MIEJSCE ZEROWE, gdy Δ=0)

d)y=2x²-4x+11
2x²-4x+11=0

Δ=b²-4ac=(-4)²-4*2*11=16-88=-72<0
Δ<0 BRAK MIEJSC ZEROWYCH

e)y=x²+3x-4
x²+3x-4=0

Δ=b²-4ac=3²-4*1*(-4)=9+16=25
√Δ=√25=5

x₁=(-b+√Δ)/2a=(-3+5)/2=2/2=1
x₂=(-b-√Δ)/2a=(-3-5)/2=-8/2=-4